Aneurysm Rupture and Mortality During the Waiting Time for a Customised Fenestrated/Branched Stent Graft in Complex Endovascular Aortic Repair. (July 2020) - Katsargyris, Athanasios; Uthayakumar, Vasuki; Marques de Marino, Pablo; Botos, Balazs; Verhoeven, Eric L.
Abstract : Objective: Treatment of complex aortic pathologies with customised fenestrated/branched stent grafts (F/BEVAR) is associated with a longer waiting time to the procedure. This study aimed to investigate the prevalence of aneurysm rupture and mortality during the waiting time for a fenestrated/branched stent graft in a single centre. Methods: All patients with a pararenal (PAA), thoraco-abdominal (TAAA), or aortic arch aneurysm planned to be treated with a customised F/BEVAR between January 2010 and December 2018 were included. Patients planned for F/BEVAR who in the end did not undergo the procedure were analysed. Results: 906 patients were planned to undergo F/BEVAR during the study period. Of those, 862 (95.1%) underwent the procedure as planned (FEVAR for PAA; n = 494, F/BEVAR for TAAA; n = 348, F/BEVAR for arch aneurysm; n = 20). In 44 (4.9%) patients, the procedure was cancelled. Thirty-seven (4.1%) patients died before the procedure, four (0.4%) patients turned down the procedure, two (0.2%) were cancelled because of worsened general condition, and one (0.1%) ruptured but underwent emergency open repair in another institution. Causes of death during the waiting time were: aneurysm rupture, n = 15 (1.7%); cardiac, n = 7 (0.8%); stroke, n = 3 (0.3%); gastrointestinal, n = 3 (0.3%); death after complete arch debranching, n = 2 (0.2%); infection, n = 2 (0.2%); death after transcatheter aortic valve implantation, n = 1 (0.1%); death after urological surgery, n = 1 (0.1%); unknown, n = 3 (0.3%). Aneurysm diameter was larger in patients who died of aneurysm rupture compared with patients who died as a result of other causes (79.2 ± 13 mm vs. 66.7 ± 12 mm, respectively, p = .005). Conclusion: Aneurysm rupture during the waiting time for F/BEVAR can occur but is rare. Patients with a larger aneurysm diameter may be at higher risk of rupture. Measures to reduce the risk of rupture during the waiting time might include the use of off the shelf devices for larger aneurysms, quicker measurement and graft plan order processes, and quicker graft construction and delivery.